An updated taxonomy of the genus Phlogacanthus (Acanthaceae) in Vietnam - Do, Hai Van; Nguyen, Mai Thi; Nguyen, Huong Thi Thanh; Choudhary, Ritesh Kumar; Deng, Yunfei (Phytotaxa, 2018)
In the present paper, taxonomic notes on the genus Phlogacanthus from Vietnam are provided. A new combination, P. datii, is proposed. A lectotype is designated for its basionym Cystacanthus datii. In addition, Phlogacanthus paniculatus is reported as a newly recorded species from Vietnam. Descriptions, illustrations, photographs and ecological notes are provided for both species. An identification key for the species of the genus Phlogacanthus from Vietnam is also provided.